Resource Capability of Local Governments in Mainstreaming Gender into Disaster Risk Reduction: Evidence from Bantul Indonesia - Yumarni, Tri; Amaratungga, Dilanthi (Journal of Regional and City Planning, 2017)
Abstract. This research aims to examine various local government capabilities for mainstreaming gender into disaster risk reduction in Bantul, Indonesia. Mixed methods, comprising qualitative and quantitative methods, were applied to explore key local government capability for effective mainstreaming gender into disaster risk reduction. There are various benefits of mainstreaming gender for enhancing disaster risk reduction. Women leadership, local government financial resources, availability of the local institutional framework, full participation of women, financial resources and effective collaboration with Non-Governmental Organizations are key capabilities that lead to effective gender mainstreaming. Keywords. Local government capability, gender mainstreaming, disaster risk reduction.Abstrak. Penelitian ini bertujuan untuk menilai kemampuan pemerintah daerah dalam mengarusutamakan gender ke dalam pengurangan risiko bencana di Bantul, Indonesia. Metode campuran, yang terdiri dari metode kualitatif dan kuantitatif, diterapkan untuk mengeksplorasi kemampuan pemerintah daerah yang menjadi kunci untuk mengarusutamakan isu gender secara efektif ke dalam pengurangan risiko bencana. Terdapat berbagai manfaat dari pengarusutamaan gender untuk meningkatkan pengurangan risiko bencana. Kepemimpinan perempuan, sumber pendanaan dari pemerintah daerah, tersedianya kerangka kelembagaan lokal, partisipasi penuh perempuan, sumber pendanaan dan kolaborasi dengan Organisasi Non-Pemerintah yang efektif adalah kemampuan kunci yang dapat menghasilkan pengarusutamaan gender yang efektif.Kata kunci. Kemampuan pemerintah daerah, pengarusutamaan gender, pengurangan risiko bencana.